Iconography in African Textiles: Exploring Kente Cloth and African Print Fabrics - ADELOYE, Adebayo Abiodun (INTELLIGENCE Journal of Multidisciplinary Research, 2026)
Traditional Textiles are major components of African cultural heritage, serving as functional items and also conveying social, spiritual, and historical meanings. The cultural significance of African textiles is gradually losing its significance among the younger generations. This study examines the iconography embedded in two prominent African textile traditions: Kente cloth and African print fabrics. The specific objectives of the study are to examine the historical origins and development of Kente cloth and African print fabrics; identify and interpret the symbolic meanings embedded in their motifs, colours, and design elements; and comparatively analyse how iconographic symbols in both textiles function as vehicles for cultural communication and identity construction. The study adopts a qualitative research design based on historical and iconographic analysis. Data were collected through document analysis of scholarly literature, visual examination of textile motifs, and archival sources on African textile traditions. The data were analysed using thematic and iconographic analysis, focusing on recurring symbolic motifs, colour symbolism, and their associated cultural meanings. Findings revealed that the design elements in these fabrics are symbolic and they reflect the values, proverbs, and philosophies of the people. Each design carries a distinct meaning, communicating moral lessons, historical events, or expressions of social status. The comparative analysis of the iconography in Kente cloth and African print fabrics revealed that they both serve the purpose of cultural expression and that their symbolic meanings can vary depending on context. It was recommended that African designers should continue to be innovative in their use of traditional motifs to suit modern tastes, so as to preserve the use of these traditional textiles in maintaining cultural identity.